A Case Discussion On Pilonidal Sinus(Nadivrana): Case Report - Sharma, Varsha; kumar sharma, Rajesh; Shah, Harshit; Padadhria, Dhruval; Kazi, Wasim (Asian Journal of Pharmaceutical Research and Development, 2023)
Pilus meaning hair and nidus meaning nest.A pilonidal sinus is an acquired condition.It is also termed as jeep disease. Mostly affected to males cause they have more hair growth. Hair containing cyst located just below the coccyx PNS occurs in the cleft between the buttocks. when buttocks moves and hair breaks off by friction and collect in the cleft makes local inflammation turns to sinus formation. PNS can be correlated with Nadivrana as per Ayurveda classic.Management of Nadi vrana is described by Susruta along with Chedana (excision) of the total tract (Su.Chi-17/18). After Chedana karma (excision) the big wound (6cm length*3cm width) was treated with local application of tikshna ApamargaKshara and Jatyadi Ghrita after cleaning wound with Panchvalkala kwath along with internal Ayurveda medicine (TriphalaGuggulu 1gm three times a day). Aim:To evaluate the efficacy of Chedana Karma and Apamarg Kshara Application in the management of shalyaja nadivrana w.s.r to Pilonidal Sinus. Methodology: here we present a case discussion of Chhedan karma and Application of tikshna Apamarga Kshara in the management of shalyaja nadivrana. Result: Patient got symptomatic relief. Conclusion: The prevalence of Nadivrana increasing day by day.Ayurvedic management is effective in slow down the disease progression and breakdown the pathology.